Computational mechanics in structural engineering : recent developments - Cheng, Franklin Y.; Gu, Yuanxian (Elsevier, 1999)
The Second Sino-US Symposium Workshop on Recent Advancement of Computational Mechanics in Structural Engineering was held between May 25-28, 1998, in Dalian, China. The objectives were: to share the insights and experiences gained from recent developments in theory and practice; to assess the current state of knowledge in various topic areas of mechanics and computational methods and to identify joint research opportunities; to stimulate future cooperative research and to develop joint efforts in subjects of common needs and interests; to build and to strengthen the long-term bilateral scientific relationship between academic and professional practicing communities. Topics discussed covered the entire field of computational structural mechanics. These topics have advanced broad applications in the engineering practice of modern structural analysis, design and construction of buildings and other structures, and in natural hazard mitigation.